An Analysis of Students’ Problems in Writing Descriptive Text at Ninth Grade SMP Negeri 42 Pekanbaru - Rosmanizar Rosmanizar; Helfianora Ofrita; Alfina Darmis (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study aims to analyze students' problems in writing descriptive texts. This research uses qualitative descriptive analysis. The population of this research is the 10th grade students SMP Negeri 42 Pekanbaru in the 2022/2023 academic year, especially in class X Building Drawings. The sample was selected using a random cluster sampling technique, with only 1 class as the research sample. Data were collected using a written test, the results of the test were analyzed using descriptive qualitative. The result of this study also showed that the students faced several problems in writing descriptive text. There were two kinds of problems found in students' writing; they were linguistic problems including grammar and vocabulary related problems, and nonlinguistic problems which include organization of ideas, content and mechanical problems. The most frequently found problems in students' writing were related to grammar and mechanical. To overcome these problems, there are some suggested solutions which include using cooperative learning or rapid writing strategy in teaching writing descriptive text. In addition, it is also suggested that a teacher should be a good teaching and learning facilitator and should also have a well-prepared teaching material which is appropriate and inspiring to the topic of teaching. Keywords: Descriptive text, Problems in Writing, qualitative descriptive analysis